2015
DOI: 10.1093/nar/gkv1006
|View full text |Cite
|
Sign up to set email alerts
|

SubtiWiki 2.0—an integrated database for the model organismBacillus subtilis

Abstract: To understand living cells, we need knowledge of each of their parts as well as about the interactions of these parts. To gain rapid and comprehensive access to this information, annotation databases are required. Here, we present SubtiWiki 2.0, the integrated database for the model bacterium Bacillus subtilis (http://subtiwiki.uni-goettingen.de/). SubtiWiki provides text-based access to published information about the genes and proteins of B. subtilis as well as presentations of metabolic and regulatory pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(134 citation statements)
references
References 23 publications
3
127
0
Order By: Relevance
“…The highly increased transcription of the MhqR regulon is also the reason for the overrepresentation of the functional category Lifestyle in protein resource allocation (see above). This category includes the stress proteins and thus also the proteins involved in resistance against oxidative and electrophile stress (see http://subtiwiki.unigoettingen.de/wiki/index.php/Resistance_against_ oxidative_and_electrophile_stress) (Michna et al 2016).…”
Section: General Results Of the Multi-omics Analysismentioning
confidence: 99%
“…The highly increased transcription of the MhqR regulon is also the reason for the overrepresentation of the functional category Lifestyle in protein resource allocation (see above). This category includes the stress proteins and thus also the proteins involved in resistance against oxidative and electrophile stress (see http://subtiwiki.unigoettingen.de/wiki/index.php/Resistance_against_ oxidative_and_electrophile_stress) (Michna et al 2016).…”
Section: General Results Of the Multi-omics Analysismentioning
confidence: 99%
“…The 2 folds threshold was used in this case to make the results comparable with the stress response regulation patterns published by Sappa et al (2013) and Kohlstedt et al (2014). Operon predictions and their transcriptional regulations were checked by using the SubtiWiki Web-based resource (Michna et al, 2015). Putative transcription regulation binding sites were identified by using the software tools provided by DBTBS server (Sierro et al, 2008; http://dbtbs.hgc.jp/).…”
Section: Gene Co-expression Analysismentioning
confidence: 99%
“…To avoid false-positive identification of untranslated regions (5'-UTR) as ncRNA, only the loci flanked by oppositely regulated genes were considered in this work. Identified sequences were compared to the records of ncRNA in SubtiWiki database (Michna et al, 2015) and those reported by Fan et al (2015) in Bacillus amyloliquefaciens FZB42. The level of sequence conservation of predicted ncRNA was checked by BLASTN search through the complete genome DNA sequences of B. subtilis ssp.…”
Section: Identification Of Differentially Expressed Non-coding Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…This resource is now routinely used by the community, providing text‐based access to published information about the genes and proteins of B. subtilis as well as presentations of its metabolic and regulatory pathways (Michna et al ., 2016). …”
Section: Databases For the Genomementioning
confidence: 99%